Phosphorus Adsorption by Soils from Four Land Use Patterns - Wang, Xiao-Yun; Zhang, Li-Ping; Zhang, Fang-Fang; Zhang, He-Si; Mei, Dao-Liang (Asian Journal of Chemistry, 2012)
This study was designed to survey the surface soils characteristics, which collected from Chinese chestnut woodland (S1), Phyllostachys edulis woodland (S2), paddy rice farmland (S3) and vegetable farmland (S4), to assess the phosphorus sorption isotherm and analyze the relationship between soil properties and sorption parameters. Results indicated that soils from paddy rice and vegetable fields were hydragric anthrosols and alluvial soils with a silt clay texture, while soils from Chinese chestnut and Phyllostachys edulis woodland were stony soils with a sandy texture. All the soils were generally acidic and pH ranged from 4.48 to 7.45. Fe-P and Ca-P contents in paddy rice and vegetable soils were higher than the contents of Chinese chestnut and Phyllostachys edulis soils. Crystalline iron oxides were the dominant forms of iron oxide in these soils. Sorption isotherm experiments showed that these soils exhibited a wide range of phosphorus sorption capacity values and the sequence of sorption capacity was S3 > S4 > S1 > S2. The Langmuir, Freundlich and Temkin models can be used to describe phosphorus sorption data, with R2 ranging from 0.75 to 0.98. The parameters of Qmax (phosphorus sorption maximum), K and B (Freundlich and Temkin adsorption constant) ranged from 71.20 to 325.11 mg kg-1, 36.51-121.15 mg kg-1 and 44.12 to 159.69 mg kg-1, respectively. Qmax, F and B had a highly significant positive relationship with pH (NaF), Ca-P, clay, Alt and Alo. About 92-99 % of the maximum phosphorus sorption capacity of these soils could be estimated by the combination of some of these properties.